2017
DOI: 10.5194/acp-2017-905
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Importance of Sulfate Radical Anion Formation and Chemistry in Heterogeneous OH Oxidation of Sodium Methyl Sulfate, the Smallest Organosulfate

Abstract: Abstract.Organosulfates are important organosulfur compounds present in atmospheric particles. While the abundance, 10 composition, and formation mechanisms of organosulfates have been extensively investigated, it remains unclear how they transform and evolve throughout their atmospheric lifetime. To acquire a fundamental understanding of how organosulfates chemically transform in the atmosphere, this work investigates the heterogeneous OH radical-initiated oxidation of sodium methyl sulfate (CH 3 SO 4 Na) dro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 28 publications
2
23
1
Order By: Relevance
“…Formation of organosulfates Based on 2009 (Hallquist et al, 2009), 2011 (Ervens et al, 2011) and 2015 (Nozière et al, 2015) review papers, aqSOA samples containing organosulfates can be produced in a laboratory framework through in-cloud chemistry under dark and/or solar conditions. In the dark mode two atmospherically relevant pathways have been suggested: (1) addition of the sulfate radicals onto an unsaturated C=C bond of the precursor (Szmigielski, 2016;Kwong et al, 2018), (2) nucleophilic addition of the sulfate anion onto an isoprene-derived epoxy ring (Darer et al, 2011;Nguyen et al, 2014). In contrast, solar approaches have entailed (1) UV irradiation of concentrated solutions of ammonium sulfate and the organic precursor (Nozière et al, 2010), (2) laser photolysis of concentrated solutions containing sulfate peroxide and carbonyl precursors (Schindelka et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Formation of organosulfates Based on 2009 (Hallquist et al, 2009), 2011 (Ervens et al, 2011) and 2015 (Nozière et al, 2015) review papers, aqSOA samples containing organosulfates can be produced in a laboratory framework through in-cloud chemistry under dark and/or solar conditions. In the dark mode two atmospherically relevant pathways have been suggested: (1) addition of the sulfate radicals onto an unsaturated C=C bond of the precursor (Szmigielski, 2016;Kwong et al, 2018), (2) nucleophilic addition of the sulfate anion onto an isoprene-derived epoxy ring (Darer et al, 2011;Nguyen et al, 2014). In contrast, solar approaches have entailed (1) UV irradiation of concentrated solutions of ammonium sulfate and the organic precursor (Nozière et al, 2010), (2) laser photolysis of concentrated solutions containing sulfate peroxide and carbonyl precursors (Schindelka et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Additionally, acetone is a polar aprotic solvent, meaning that it cannot donate protons (H + ) since it lacks a hydroxyl group, which sets it apart from the other alcohols. 27 This lack of hydrogen donation in the acetone leads to less interaction with the anions (SO 4 –2 ) in the solution. Also, the oxygen in the carbonyl group can interact via hydrogen bonding with water that surrounds the nanoparticles, cations, and anions in the solution, which is related to desolvation described above.…”
Section: Discussionmentioning
confidence: 99%
“…Since methanol has a hydroxyl group, it can donate a proton, thus increasing the interaction with anions in the solution and at the liquid/particle interface. 27 This increased anion interaction will hinder the nucleation of nanoparticles and interaction at their surface by reducing cation interaction. Also, since it is a longer chain, there is a slight decrease in the solubility of methanol with water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where ρ0 and ρw are the density of the dry sample and water, respectively. The density of methyl-, ethyl-and octyl-OS particles were reported to be 1.60, 1.46 and 1.19 g cm -3 with an uncertainty of 20-30% (Kwong et al, 2018;ChemistryDashboard, 2021). Figure 6 compares VSA-derived GFs and those measured using H-TDMA for methyl-, ethyl-and octyl-OS, and it can be concluded that for RH at which samples used in the VSA experiments were deliquesced, GFs derived from mass change measured using VSA agree relatively well with those directly measured using H-TDMA.…”
Section: Comparison Between Vsa and H-tdma Measurementsmentioning
confidence: 99%